Orchestra in Digital Transformation: Expanding Perceptual Possibilities of Classical Music with a Hybrid Performance Format - Lara; Buschmann, Renate (Mimesis Journal, 2024)
The article analyses a multimedia concert practice ‘Raumkonzert’ (‘expanded concert’, 2019-2022), which aims to create a walkable musical space by inviting the musicians to play in separate rooms while being connected to each other and to the conductor via digital equipment. This allows the visitors to experience the spatially expanded musical performance in an open and participatory “pick your own adventure” fashion. As the authors have acted as curators for one such concert, they explore the transformative and aesthetic potential of this format as well as its historical precursors and elaborate on the process of its site-specific execution.